Konsistensi Politik Hukum Dalam Pembentukan Undang-Undang Pasca Reformasi - Rohma Sari; Gokma Toni Parlindungan S; Amanda Bherlyana Putri; Suci Nurjannah Yuansyah; Nabilla Amanda Putri (Universitas Sumatera Barat, 2025)
Post-1998 Reformation, the Indonesian state system experienced a fundamental shift, including in the aspect of legal politics. The laws that were formed should reflect the direction of legal politics that are consistent with the ideals of reform, namely law enforcement, democracy, and protection of human rights. However, in practice, many legislative products show inconsistencies between normative goals and practical-political interests. This study aims to analyze the extent of the consistency of Indonesian legal politics in the formation of laws after the reformation. By using a normative and evaluative approach to several strategic laws after the reformation, it was found that intervention of power, weak public participation, and inconsistency of legislative principles are the main challenges. This study recommends strengthening legislative planning based on the legal needs of the community and improving national legislative governance.